Achieving long lifetime of room-temperature phosphorescence via constructing vitrimer networks. (15th March 2022) - Gao, Yulei; Deng, Zhou; Wang, Fenfen; Sun, Pingchuan
Abstract : Fluorescence and RTP dual emission polymers exhibit reversible temperature responsiveness, tunable mechanical properties, remarkable thermostability and thermo-adaptive self-healing ability based on a dynamic covalently crosslinked 3D network. Abstract : Pure organic polymer materials exhibiting room-temperature phosphorescence (RTP) are highly desired for optoelectronic and biomedical applications. Covalent bonding of phosphors into a polymer matrix has been found to be successful in constructing efficient RTP materials owing to the substantial roles of the polymer matrix in restricting the molecular motion of phosphors and activating RTP emissions, thus fabricating new covalently crosslinked high-performance RTP materials is of great significance. Herein, a reasonable RTP system is constructed by covalently linking the phosphor (BF2 epo) into an epoxy-based vitrimer network to obtain fluorescence and RTP double emissions. The 3D crosslinked polymer network structure restricts the molecular motion of BF2 epo, depresses nonradiative transition and shields quenchers effectively. By altering the content of BF2 epo, polychromatic photoluminescence and long phosphorescence lifetime are achieved under air conditions. The RTP emission intensity of this vitrimer material can respond to two different stimuli of ammonia and temperature, making it possible to work as sensors with good mechanical properties. Furthermore, the topology rearrangement of a dynamically crosslinked network structure endows this dual emission vitrimer with potential prospects in applications such as device fabrication and processing because of the advantages of excellent thermomechanical properties, high thermal stability, and self-repairing properties.